Haliotis tuberculata, a generalist marine herbivore that prefers a mixed diet, but with consistent individual foraging activity. (6th March 2020) - Roussel, Sabine; Poitevin, Pierre; Day, Robert; Le Grand, Fabienne; Stiger‐Pouvreau, Valérie; Leblanc, Catherine; Huchette, Sylvain
Abstract: While population foraging behaviour of herbivores has been extensively studied, individual choice is still poorly understood. Very few studies have focused on the individual consistency of foraging behaviour in marine herbivores. Because marine ectotherms are strongly influenced by their environment and because a mixed diet is appropriate for herbivores, we hypothesized that Haliotis tuberculata, a large marine gastropod, would not exhibit significant individual consistency in foraging activity and would display generalist food choices. To test these hypotheses, the behaviour of 120 abalone was studied using a choice test of eight macroalgal species over 3 weeks, with video recording 24 hr a day. In addition, primary components, secondary metabolites and toughness of the eight algae were measured. At the population level, food choice was mainly related to the protein composition and the toughness of the macroalgae. We found that H. tuberculata is a generalist species feeding on a variety of algae (IS = 0.64), even if 21% of the individuals can be considered to be specialists. However, in contrast to our hypothesis, highly consistent between‐individual variation was observed in foraging activity (ICC = 0.81 for time spent feeding and ICC = 0.74 for number of feeding visits per day). The high individual consistency of foraging activity has some ecological and evolutionary implications currently not understood for this marine herbivore. Abstract : Number of feeder visits initiated each 2‐hr period of the 24‐hr cycle of Haliotis tuberculata . Eight abalone per tank were observed for 4 days per week during a 3‐week period in a total of 15 tanks. Mean ± SE Key‐findings: H. tuberculat a is a generalist species in term of algal choice, with a small proportion of the individuals being specialists and the majority being generalists. In addition, individual foraging activity pattern was highly consistent over time, with some abalone feeding every night while others fed only rarely. Algal preferences probably result from a compromise between the most useful algae from a nutritional point of view, the physical ability of abalone to consume the food item and some individual consistency.